Field notes and Barbara L. Wilson letter to Carl J. Bendorf, fall 1986 - Wilson, Barbara L.et al (1986)
List of birds and locations contributed by Barbara L. Wilson. Included with the field notes is a letter from Barbara L. Wilson to Carl J. Bendorf regarding the mild, wet fall weather. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1986. Epson - sheet feed/flatbed